Understanding dropout in the athlete development process - Larsen, C. H.; Alfermann, D. (Routledge handbook of talent identification and development in sport, 2017)
The purpose of this chapter is to summarize the research and to broaden our understanding of dropout in the athlete development process. First, we provide a description of different terminologies related to dropout. Second, we describe dropout as a mismatch between resources and demands. Third, we look into personal, lifestyle and sporting reasons associated with dropout. Fourth, we outline athletes` characteristics associated with dropout. Fifth, we describe coaches` and parents` contributions to dropout and subsequently illustrate further environmental factors associated with dropout. Sixth, we provide a summary of factors that prevent dropout and promote continuation; and seventh and finally, we provide strategies, applied perspectives and recommendations for how to prevent dropout of athletes.